2015
DOI: 10.1128/aem.03018-14
|View full text |Cite
|
Sign up to set email alerts
|

Few Highly Abundant Operational Taxonomic Units Dominate within Rumen Methanogenic Archaeal Species in New Zealand Sheep and Cattle

Abstract: Sequencing and analyses of 16S rRNA gene amplicons were performed to estimate the composition of the rumen methanogen community in 252 samples from eight cohorts of sheep and cattle, separated into 16 different sample groups by diet, and to determine which methanogens are most prominent in the rumens of farmed New Zealand ruminants. Methanobacteriales (relative abundance ؎ standard deviation, 89.6% ؎ 9.8%) and Methanomassiliicoccales (10.4% ؎ 9.8%) were the two major orders and contributed 99.98% (؎0.1%) to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 46 publications
23
65
1
Order By: Relevance
“…However, these taxa were characterized by OTUs different than those in 8 week old calves, indicating continued species-level differences as animals age. Both adult rumen and fecal archaeal communities were dominated by Methanobrevibacter OTUs that were different from those in calves, confirming previous reports2642. The adult archaeal microbiota was also more diverse than at weaning, likely as a result of the more diverse adult microbiota providing multiple substrates and methanogenic niches.…”
Section: Discussionsupporting
confidence: 84%
“…However, these taxa were characterized by OTUs different than those in 8 week old calves, indicating continued species-level differences as animals age. Both adult rumen and fecal archaeal communities were dominated by Methanobrevibacter OTUs that were different from those in calves, confirming previous reports2642. The adult archaeal microbiota was also more diverse than at weaning, likely as a result of the more diverse adult microbiota providing multiple substrates and methanogenic niches.…”
Section: Discussionsupporting
confidence: 84%
“…Unlike buffalo, many cattle studies have reported presence of Methanosphaera in moderate abundance [8,29]. In cattle, several studies have reported presence of Methanomassiliicoccales or RCC clade of Thermoplasmata [30,31]. In the rumen, methanol is a product of pectin hydrolysis by protozoa and esterase activity of bacteria.…”
Section: Discussionmentioning
confidence: 94%
“…In rumen, the aceticlastic pathway was not important with low numbers of Methanosarcina retrieved [13,14]. Recent years, methylotrophic Methanomassiliicocales, which was one of the most important methanogens populations [15,16], was found to be abundant in some rumens [17].…”
Section: Introductionmentioning
confidence: 99%